Efeito de métodos de determinação de parâmetros para o controle da irrigação na eficência do uso da água do feijoeiro, sob três diferentes lâminas de água no solo - Chieppe Jr., João Baptista (2008)
The objective of this research was to study three methods of parameter determination for irrigation control under different tensions in common bean (Phaseolus vulgaris L.). The treatments were a combination of three methods of parameter determination for irrigation control (tensiometer, water retention curve, USWB Class A pan) with three soil water tensions (1:-30 kPa; 2:-60, kPa both for the whole plant cycle; 3:-60 kPa for the vegetative phase and -30 kPa for the reproductive phase). The experimental design was randomized blocks, factorial 32 with three replicates. Although no significant effect on water use efficiency was found, a tendency for increasing water use efficiency in treatments with tensions of -60 kPa at the vegetative phase and -30 kPa at the reproductive phase was observed in all methods of parameter determination for irrigation control. Water was saved as less irrigation was applied during the vegetative phase and more irrigation at the reproductive phase. No precipitation was observed from June to September 1995, leading to a high yield and therefore to a higher water use efficiency.